Phylogenetic and Genetic Variation Analysis of ITS1 Gene of Trypanosoma lewisi in Wild Rats Using Polymerase Chain Reaction - Yesica, Reza; Hardian, Andreas Bandang; Oktanella, Yudit; Kusumarini, Shelly; Prasetyo, Gabriela Jeanne Giacynta (Jurnal Medik Veteriner, 2024)
Murine Trypanosomiasis is a disease caused by the blood protozoan Trypanosoma lewisi in rats, with the transmission process mediated by the flea species Xenopsylla cheopis and Nosopsyllus fasciatus. Cases of trypanosomiasis have been documented due to Trypanosoma lewisi infecting rats and humans in various countries. Diagnosis of T. lewisi is typically conducted using polymerase chain reaction (PCR), which amplifies target DNA using specific primers. One such target gene for detection is the Internal Transcribed Spacer-1 (ITS1). Subsequent sequencing of PCR products enables analysis of genetic variation employing parameters such as nucleotide composition, genetic distance, and phylogenetic analysis with MEGA software. Test results based on percent identity values indicated a 98.51% homology of blood samples with the Chinese strain of T. lewisi (FJ011094.1), demonstrating genetic variation. Phylogram reconstruction revealed that samples 18, 19, and 37 of T. lewisi exhibit very close intraspecies relationships with T. lewisi from NCBI genebank with genetic distance ranging from 0.007 to 0.01. While the closest interspecies relationship was found with T. cruzi (KT305857.1) with a genetic distance of (d = 0.61).